EFFECT OF MORINGA LEAF (Moringaolefera) FLOUR ADDITION ON THE QUALITY OF MACARONI CATFISH(Pangasius hypophthalmus) - Oktavia Rimanda; Desmelati Desmelati; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aimed to determine the effect of moringa leaf flour on the quality of macaronicatfish and increasingdietary fiber content. The research method was the experiment using a non-factorial Complete Randomized Design (CRD) with 4 levels of treatment, namelyMk0 (without moringa leaf flour), Mk1 (60 grams moringa leaf flour), Mk2 (90 grams moringa leaf flour), Mk3 (120 grams moringa leaf flour). The tested parameters were organoleptic analysis (appearance, aroma, taste and texture) and, proximate analysis (moisture content, ash content, protein content, fat content and dietary fiber content). The results showed that the addition of moringa leaf flour in macaroni catfish products had a significant effect(P<0.05) on the quality of macaroni catfish. Mk16% (60 grams) was the best treatment with green characteristics, the aroma of sufficiently fish and moringa leaves, the taste of sufficiently fish and moringa leaves, and crispy texture. The proximate value ofMk1was 6.78% moisture content, 6.42% ash content, 23.74% protein content, 41.73% dietary fiber content, and 10.55% fat content.Keywords: Catfish, macaroni,moringa leaf flour, and quality